What do poor women want? Public employment or cash transfers? Lessons from Argentina - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2012)
The literature on public employment policies such as the job guarantee (JG) and the employer of last resort (ELR) often emphasizes their macroeconomic stabilization effects. But carefully designed and implemented policies like these can also have profound social transformative effects. In particular, they can help address enduring economic problems such as poverty and gender disparity. To examine how, this paper will look at the reform of Argentina's Plan Jefes into Plan Familias. Plan Jefes was the hallmark stabilization policy of the Argentine government after the 2001 crisis. It guaranteed a public sector job in a community project to unemployed male and female heads of households. The vast majority of beneficiaries, however, turned out to be poor women. For a number of reasons that are explored below, the program was later reformed into a cash transfer policy, known as Plan Familias, that still exists today. The paper examines this reform in order to evaluate the relative impact of such policies on some of the most vulnerable members of society; namely, poor women. An examination of the Argentine experience based on survey evidence and fieldwork reveals that poor women overwhelmingly want paid work opportunities, and that a policy such as the JG or the ELR cannot only guarantees full employment and macroeconomic stabilization, but it can also serve as an institutional vehicle that begins to transform some of the structures and norms that produce and reproduce gender disparities. These transformative features of public employment policies are elucidated by turning to the capabilities approach developed by Amartya Sen and elaborated by Martha Nussbaum - an approach commonly invoked in the feminist literature. This paper examines how the access to paid employment can enhance what Sen defines as an individual's 'substantive freedom'. Any policy that fosters genuine freedom begins with an understanding of what the targeted population (in this case, poor women) wants. It then devises a strategy that guarantees that such opportunities exist and removes the obstacles to accessing these opportunities.
Keywords: B54; D02; D13; D31; D63; E24; E26; E62; E65; H31; H41; H53; I38; 330; capabilities approach; employer of last resort; job guarantee; basic income; cash transfers; public employment; gender inequality; poverty; Plan Jefes; Plan Familias; Argentina